HUBUNGAN ANTARA MOTIVASI BELAJAR DAN PERHATIANORANGTUA DENGAN PRESTASI BELAJAR KEJURUAN OTOMOTIF SISWA KELAS XI SMK NEGERI 2PRAYA TENGAH NUSA TENGGARA BARATTAHUN PELAJARAN2014/2015 - Rodi Mahendra Husaen; Suparmin Suparmin (Jurnal Taman Vokasi, 2015)
This study aimed to know (1) correlation between learning motivation with the learning achievement of automotive vocational; (2) correlation between parents’ attention with the learning achievement of automotive vocational; and (3) correlation between learning motivation and attention parentstoward the learning achievement of automotive vocational among the eleventh grade students of state vocational school 2 Central Praya West Nusa Tengara in academic year 2014/2015. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double correlation. This study shows that (1) there was a positive and significant correlation between learning motivation with the learning achievement of automotive vocational among the eleventh grade students of state vocational school 2 Central Praya WestNusa Tengara in academic year 2014/2015 with the significant score 0,000 < 0,05; (2) there was a positive and significant correlation between attention parentswith the learning achievement of automotive vocational among the eleventh grade students of state vocational school 2 Central Praya Nusa Tengara Barat in academic year 2014/2015 with the significant score 0,000 < 0,05; and (3) there was a positive and significant correlation between learning motivation and parents’ attention toward the learning achievement of automotive vocational among the eleventh grade students of state vocational school 2 Central Praya WestNusa Tengara in academic year 2014/2015 with the significant score 0,000 < 0,05.